Oxidation Behavior of Bi(Pb,Ga) SrCaCuO System - Balci, Y.; Ceylan, M.; Aksan, M. A.; Yakinci, M. E. (Springer, 2011)
A nominal compositions of BiSrCaCuO (3:2:2:3), (2:2:2:3), (4:3:3:4), and BiPbGaSrCaCuO (3:0.5:2:2:3), (3:0.3:0.3:2:2:3) have been prepared by conventional melt-quenching method. The oxidation behaviors of samples prepared were analyzed using a thermogravimetric analyser, TGA. Total mass gains of samples, average oxidation rates and maximum oxidation rates were calculated separately. TGA measurements of all samples were carried out under the normal atmosphere pressure.
Keywords: BSCCO superconductors; Oxidation; Glass-ceramic HTc superconductors